Someone is watching : a novel - Fielding, Joy (Ballantine Books, 2015)
"Deeply shaken after a brutal attack, Bailey Carpenter struggles to reclaim control over what had once seemed like a neatly-ordered life. Unable to face her job, her friends, or even the world outside her apartment, Bailey is trapped with her thoughts, replaying the attack in a desperate search for a detail that will help the police uncover the identity of her unknown assailant. Bailey sees her attacker in the face of every stranger, and is unable to trust anyone other than her half-sister, Claire, and Claire's snarky teenage daughter Jade. To pass the time in her lonely apartment, Bailey plays with the binoculars she once used in her career as a private investigator, scanning the high-rise buildings around hers for entertainment. She quickly discovers a favorite source: a handsome, wealthy playboy in the apartment across the street. But she watches him strut around his bedroom, she starts to wonder if he's putting on a show - with her as his intended audience. Looking out the window late one night, she sees him looking tauntingly right back at her, binoculars in hand. Could it be the assailant she's been so desperate to identify has been right there, watching her, the whole time? The police, exasperated after Bailey's many paranoid false alarms, believe she's crying wolf, and Claire tries to convince her she's wrong. Doubting her own sanity, Bailey has only Jade left to turn to, and together the two hatch a dangerous plot to discover just what exactly is going on in the apartment across the way"--